From Microns to Meters: Exploring Advances in Legume Microbiome Diversity for Agroecosystem Benefits - Schaedel, Marie; Hidrobo, Gabriela; Grossman, Julie (Frontiers in Sustainable Food Systems, 2021)
Legumes are of primary importance for agroecosystems because they provide protein-rich foods and enhance soil fertility through fixed atmospheric nitrogen. The legume-rhizobia symbiosis that makes this possible has been extensively studied, from basic research on biochemical signaling to practical applications in cropping systems. While rhizobia are the most-studied group of associated microorganisms, the functional benefit they confer to their legume hosts by fixing nitrogen is not performed in isolation. Indeed, non-rhizobia members of the rhizosphere and nodule microbiome are now understood to contribute in multiple ways to nodule formation, legume fitness, and other agroecosystem services. In this review, we summarize advances contributing to our understanding of the diversity and composition of bacterial members of the belowground legume microbiome. We also highlight applied work in legume food and forage crops that link microbial community composition with plant functional benefits. Ultimately, further research will assist in the development of multi-species microbial inoculants and cropping systems that maximize plant nutrient benefits, while reducing sources of agricultural pollution.